2003
DOI: 10.3171/jns.2003.99.1.0106
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of intracranial nongerminomatous malignant germ cell tumors by administering neoadjuvant chemotherapy and radiotherapy before excision of residual tumors

Abstract: Neoadjuvant therapy, consisting of combined chemo- and radiotherapy, followed by complete excision of residual tumors is highly effective in patients with intracranial NGMGCTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 25 publications
1
44
0
1
Order By: Relevance
“…Excellent results have been reported in patients in the poor prognosis group treated with neoadjuvant therapy, consisting of combined chemotherapy and radiation therapy, followed by complete resection of residual tumors, and all 7 patients survived for 39-177 months. 15 In our series, 2 patients, in whom gross-total resection was not achieved because of the tumor's anatomical location, experienced rapid growth and dissemination of the tumor, suggesting that more intensive neoadjuvant therapy is necessary to allow complete resection in the treatment of tumors in the poor prognosis group. Third, histological examination of the specimens from salvage surgery demonstrated that the treatment-resistant components consisted of fibrous tissue and yolk sac tumor or choriocarcinoma in the poor prognosis group, in contrast to teratoma or scar in the intermediate prognosis group.…”
Section: Treatment Of the Intermediate Prognosis And Poor Prognosis Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Excellent results have been reported in patients in the poor prognosis group treated with neoadjuvant therapy, consisting of combined chemotherapy and radiation therapy, followed by complete resection of residual tumors, and all 7 patients survived for 39-177 months. 15 In our series, 2 patients, in whom gross-total resection was not achieved because of the tumor's anatomical location, experienced rapid growth and dissemination of the tumor, suggesting that more intensive neoadjuvant therapy is necessary to allow complete resection in the treatment of tumors in the poor prognosis group. Third, histological examination of the specimens from salvage surgery demonstrated that the treatment-resistant components consisted of fibrous tissue and yolk sac tumor or choriocarcinoma in the poor prognosis group, in contrast to teratoma or scar in the intermediate prognosis group.…”
Section: Treatment Of the Intermediate Prognosis And Poor Prognosis Nmentioning
confidence: 99%
“…Previous stud-ies have also demonstrated excellent results with salvage surgery and subsequent chemotherapy in the treatment of tumors in the intermediate prognosis group. 15,38 The poor prognosis group showed 3 characteristic patterns of recurrence and response to the treatment. First, tumor progression occurred very early, even during the initial treatment, which reflects the aggressiveness of these tumors.…”
Section: Treatment Of the Intermediate Prognosis And Poor Prognosis Nmentioning
confidence: 99%
“…6,11,18) However, a recent study found that patient survival in both groups has improved due to updated microsurgical techniques, combination multidrug chemotherapy and radiotherapy, and improved brain MR imaging. 12,15,16,29) Yolk sac tumors are hypervascular 1,8,11,18,19,25,28) and, in our case, the tumor bled heavily during dissection. Accordingly, we recommend that angiography be performed before surgery.…”
Section: Discussionmentioning
confidence: 94%
“…Other reports also recommend chemotherapy and/or radiotherapy before surgery to shrink the tumor and facilitate surgical intervention. 7,12,29) Taken together, these recommendations will prevent tumor dissemination during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…20 It is recognized that, in older children, chemotherapy with platinum agents is effective for intracranial immature teratomas. 11,15,16 It is also known that neoadjuvant chemotherapy can induce differentiation of malignant germ cell tumors into mature teratomas. 8 The apparent tumor maturation presumably reflects the selective chemo-ablation of their actively proliferating components.…”
Section: Discussionmentioning
confidence: 99%